ANALYSIS OF FACTORS INFLUENCING THE VALUE OF PROPERTY AND REAL ESTATE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Adzedora M. Lopes Da Cruz; Stanis Man; Rere Paulina Bibiana (Jurnal Ekonomi, 2023)
This study aims to determine the effect of capital structure, liquidity, and firm size on firm value with profitability as the intervening variable. The research sample was determined using a purposive sampling method of 57 company financial statements, and the data was processed using SmartPLS software. The results of this study shows that all independent variables have an effect on the dependent variable and the intervening variable is able to mediate the effect of the independent variables on the dependent variable.